Regulation of noradrenaline synthesis, uptake, and degradation in the left ventricle by fatty acid amide hydrolase (FAAH) inhibitor URB597 in the chronic unpredictable stress model of depression - Ferizović, Harisa; Spasojević, Nataša; Janković, Milica; Stefanović, Bojana; Dronjak, Slađana (Archives of Biological Sciences, 2024)
Paper description: Depressive patients are likely to experience cardiovascular disease. Pharmacological suppression of fatty acid amide hydrolase (FAAH) activity presents a promising approach for treating mood disorders. An animal model of depression was used to assess the effects of FAAH inhibitor URB597 on noradrenaline levels and catecholamine turnover in the left ventricle in both sexes. URB597 treatment led to increased expression of dopamine-β-hydroxylase (DBH) in stressed males, elevated noradrenaline transporter (NET), and decreased monoamine oxidase-A (MAO-A) levels in the left ventricle of stressed rats of both sexes. Our results offer insight for developing new treatments for comorbidity of depression and heart disease. Abstract: Depression has been linked to the dysfunction of the autonomic nervous system, which may cause dysregulation of the cardiovascular system. One promising therapeutic strategy for treating different diseases is inhibiting the enzyme fatty acid amide hydrolase (FAAH), which increases the availability of endogenous cannabinoids. We examined the effect of chronic FAAH inhibition with URB597 treatment on the noradrenaline (NA) content, synthesis, transport, and degradation in the left ventricle of female and male rats exposed to chronic unpredictable stress (CUS). CUS decreased the levels of both NA and dopamine-β-hydroxylase (DBH) protein in male rats and decreased NA transporter (NET) protein levels in female rats while elevating monoamine oxidase A (MAO-A) in both sexes. Intraperitoneal URB597 application led to increased expression of DBH in stressed males, as well as elevated NET protein levels and decreased MAO-A protein levels in the left ventricle of stressed rats of both sexes. URB597 treatment may have a beneficial effect on the cardiovascular system in an animal model of depression with heightened sympathoneural activity.